Installation of precast reinforcement concrete (R.C) piles for double-storey building / Noor A’kashah Amir Hamzah - Amir Hamzah, Noor A’kashah (Universiti Teknologi Mara, Perak, 2018)
This report is about all the information about the case study through practical training under Jabatan Kerja Raya (JKR) Daerah Bera. The topic of the practical training report is The Installation of Precast Reinforcement Concrete (R.C) Piles for Double-Storey Building. The selected topic is based on the work in progress at the construction site which is the substructure works. In this report, the are 5 main chapter which tells about the general information of the organization, the information of selected specific topic for the practical training report, the problems and also the recommendations that have been identified during the progress of the works. In chapter 1, it is about the information of the organization that I have undergoing my practical training. The scope of works, the function of the organization and the main structure of the organization have been identified. In chapter 2, it is about the details information from literature review based on the topic selected at the case study. From this chapter, it contents the definitions, functions, types and explanations. In chapter 3, it about the details information of the case study. The sequences of the works progress, data and results are based on the experiences and observation at the real construction site. In chapter 4, it concerns the identified problems occurring on the site construction. The recommendation works to the problems have been attached in the way to get the best result of the construction.